PENGARUH DAYA TARIK TERHADAP KEPUASAN WISATAWAN DI COFFEE ON THE BUS PO. REJEKI TRANSPORT YOGYAKARTA - Benediktus Primus Gunteja; Enny Mulyantari; Arif Dwi Saputra (Journal of Tourism and Economic, 2021)
This study aims to determine whether the tourist attraction factors which consist of attractions, amenities, and accessibility have an effect on tourist satisfaction at Coffee On The Bus PO. Fortune Transport. The research sample was 50 tourist respondents who visited the Coffee on The Bus. This type of research is a type of quantitative research using multiple linear analysis located in Yogyakarta. The results showed that the three variables simultaneously and significantly affected tourist satisfaction.